If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 5 + -3(x + 1) = 9x + 7 Reorder the terms: 6x + 5 + -3(1 + x) = 9x + 7 6x + 5 + (1 * -3 + x * -3) = 9x + 7 6x + 5 + (-3 + -3x) = 9x + 7 Reorder the terms: 5 + -3 + 6x + -3x = 9x + 7 Combine like terms: 5 + -3 = 2 2 + 6x + -3x = 9x + 7 Combine like terms: 6x + -3x = 3x 2 + 3x = 9x + 7 Reorder the terms: 2 + 3x = 7 + 9x Solving 2 + 3x = 7 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 2 + 3x + -9x = 7 + 9x + -9x Combine like terms: 3x + -9x = -6x 2 + -6x = 7 + 9x + -9x Combine like terms: 9x + -9x = 0 2 + -6x = 7 + 0 2 + -6x = 7 Add '-2' to each side of the equation. 2 + -2 + -6x = 7 + -2 Combine like terms: 2 + -2 = 0 0 + -6x = 7 + -2 -6x = 7 + -2 Combine like terms: 7 + -2 = 5 -6x = 5 Divide each side by '-6'. x = -0.8333333333 Simplifying x = -0.8333333333
| 5k+6=2k+12 | | 7x+3y=44 | | 8/z^2-3/z^3 | | 6(t-6)+8t=7(2t+4)-8 | | 5(-53/4x)=-65/2 | | 28y=39(9y-6) | | 2.94x^2-24.99x-13.23=0 | | (63x^9)/9 | | 5y+1.8-4y=-3.2 | | x=2.5+3y | | x-3+4x=-7x-5x | | 8x-4y-2y+7x+10= | | 0.2(30)=0.4(50+x)-0.8x | | 2/3(8+4x)=104/3 | | 1/7x+3/4x | | 3/5x=1/2x+2 | | b+4b+8=16b+4 | | 4/5n+3-2/3n=1/2-3n | | 8(x+1)-(5x-1)=1 | | X^6+36=100 | | 2x^2-2=7x | | .5y+.5-y=.25 | | X(x)+10x+25=36 | | 7(x+5)-(4x-1)=2 | | 25x^2-20x+4=25 | | 9t+t= | | 3(x-3)=13x-21 | | 8(x+5)-(3x-5)=7 | | 12n+8=11 | | -3x+8x-2= | | 3x^4=24 | | 2x+38-3x=1-9x+5 |